Three Views of a Secret: The "Mønsterlig" - Muir, Tom (Kvinder, Køn & Forskning, 2017)
In a world where English – and its attendant writing conventions – is the dominant language of research, it becomes increasingly important to explore academic patterns of writing and teaching, and their related etymologies. In particular, this article investigates the relationship between the Norwegian “mønster” and the English “monster”, arguing that monsters allow us to make space for new kinds of writing, new languages of thought. Monstrosity, and monstrous patterns – meanings that are available in Norwegian rather than English – let slip alternative ways of thinking about teaching, writing and teaching writing. This is done through an exploration of the work of the literary critic Barbara Johnson, who gives us three uncanny topics – prosopopoeia, monuments and repetition compulsion – that help us release the warnings (Latin: “monere”) from mønstre (Norwegian: “patterns”). The article argues that prosopopoeia, monuments and repetition can help us to hear the monster within mønstrene (the patterns). At the same time, the paper seeks a critical self-awareness of its status as an English language text about a Norwegian word. Acknowledging that these conventions are themselves historical and cultural artefacts – are mønstre – the article therefore tries to interrupt and unravel itself in the hope of making space for alternative kinds of writing.